Emotional Education Program: “Aventurémonos en Familia”: A strategy for the promotion of mental health, family functionality and the prevention of violence - Russo de Sánchez, Ana Rita; Reales Silvera, Liceth Paola; Mayor Molinares, Diana Paola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
“Aventurémonos en Familia Program” aims to generate a space for the recognition, regulation and emotional recovery of early childhood, children, teenagers and their families in the midst of the crisis presented by Covid-19, and who are immersed in contexts of violence. This is an emotional education program, its objective is promoting mental health and family functionality. In the program was implemented a mixed research with 159 caregivers and 139 children in Córdoba, Atlántico and Sucre, Colombia. The results show that the participants have improvements family functionality and the emotional skills of the family members.